Modifying rates of reductive elimination of leaving groups from indolequinone prodrugs: a key factor in controlling hypoxia-selective drug release. - Everett, SA; Swann, E; Naylor, M; Stratford, MR; Patel, K; Tian, N; Newman, R; Vojnovic, B; Moody, C; Wardman, P (2002)
3-(4-Methylcoumarin-7-yloxy)methylindole-4,7-diones were synthesised as model prodrugs in order to investigate the correlation between rates of reductive elimination from the (indolyl-3-yl)methyl position with reductive metabolism by hypoxic tumor cells and NADPH: cytochrome P450. Rates of elimination of the chromophore/fluorophore (7-hydroxy-4-methylcoumarin) following one-electron reduction of indolequinones to their semiquinone radicals (Q*-) was measured by pulse radiolysis utilising spectrophotometric and fluorometric detection. Incorporation of a thienyl or methyl substituent at the (indol-3-yl)CHR-position (where R=thienyl or methyl adjacent to the phenolic ether linking bond) significantly shortened the half-life of reductive elimination from 87 to 6 and 2 ms, respectively. Elimination from the methyl substituted analogue can thus compete effectively with the reaction of the semiquinone radical with oxygen at levels typically present in tumours (half-life approximately 1.8 ms at 0.5% O2). Chemical kinetic predictions were confirmed by metabolism in breast tumour MCF-7 cells between 0-2.1% O2. Rates of reductive release of the fluorophore from the non-fluorescent parent indolequinones (R=H, Me, thienyl) were similar under anoxia ( approximately 1.7 nmol coumarinmin(-1)mg protein(-1)) reflecting the similarity in one-electron reduction potential. Whereas coumarin release from the indolequinone (R=H) was completely inhibited above 0.5% O2, the enhanced rate of reductive elimination when R=thienyl or Me increased the metabolic rate of release to approximately 0.35 and 0.7 nmol coumarinmin(-1)mg protein(-1), respectively at 0.5% O2; complete inhibition occurring by 2.1% O2. Similar 'oxygen profiles' of release were observed with NADPH: cytochrome P450 reductase. In conclusion, it is possible to modify rates of reductive elimination from indolequinones to control the release of drugs over a range of tumour hypoxia.